Evolution of Telecommunications Networks Under Imprecise Demands 10.14209/jcis.2001.10 - M. F. Carlson, Carlos; M. F. Tavares, Hermano; R. F. Formigoni, Jose (Journal of Communication and Information Systems, 2015)
New services and technologies, as well as the very competitive environment, increase the significance of planning the expansion of telecommunications systems. Multiple ways for network evolution and their related cost claim for comprehensive and flexible planning tools. Mathematical models can also be used. However, at planning time there is uncertainty with respect to some data values. Thus, models must incorporate and deal with uncertainty. Keeping this in mind, it is presented a class of models for planning a stage of the evolution of telecommunications networks, namely, the optical serving of business subscribers (key customers). These models accept imprecise demand values, using a fuzzy numberbased approach. It is possible to analyze several aspects of the contest between fiber-and copper-based systems. Enabling the evaluation of the impact of varying demands onto the planned network is also a key feature of the models. A case study with actual data is reported.